Consonant Sequence Phonemes In Indonesian - Nisa Aldira Lubis; Anisa May Azura; Yani Lubis (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Phoneme series are two different phonemes that are located side by side, but are in different syllables (syllables). Research method In this study, the researcher used a type/research approach in the form of Library Research. Literature study is a study that is used to collect information and data with the help of various materials in the library such as documents, books, magazines, historical stories.